2020
DOI: 10.1149/1945-7111/aba00c
|View full text |Cite
|
Sign up to set email alerts
|

Function of Sulfhydryl (–HS) Group During Microvia Filling by Copper Plating

Abstract: In this work, 3-mercapto-1-propanesulfonate (MPS) with one sulfhydryl (-HS) group and 2,3-dimercapto-1-propanesulfonate (DMPS) with two -HS groups were used as model additives to reveal the function of -HS group during copper plating. Chronopotentiometry was employed to characterize the different electrochemical behaviors of the two model additives. It indicated that DMPS showed stronger accelerating effect than MPS in the plating bath containing Cl − , which could be attributed to its enhanced adsorption caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In order to ensure that the micropores are filled with non-porous and are completely filled, copper needs to grow from the bottom of the blind hole step by step from the bottom to the top during the electrodeposition process, which is achieved through the coordination of several additives [5][6][7]. Currently, three types of additives including suppressor represented by macromolecular polyether compounds (such as polyethylene glycol (PEG) [8][9][10], polypropylene glycol [11,12]), accelerator represented by propane sulfonate derivatives (such as sodium 3-mercapto-1propane sulfonate [13,14] and bis (3-sulfopropyl) disulfide (SPS) [15][16][17]), levelers represented by heterocyclic or alkyl compounds (such as Janus Green B, Diazine Black and Alcian Blue [18][19][20]). Among them, suppressors with larger molecular chains combine with Cl − and are usually adsorbed on the surface of the circuit board to form a chelate with Cu 2+ or Cu + to inhibit the deposition rate of copper, thereby reducing the current density of the blind hole orifice [8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure that the micropores are filled with non-porous and are completely filled, copper needs to grow from the bottom of the blind hole step by step from the bottom to the top during the electrodeposition process, which is achieved through the coordination of several additives [5][6][7]. Currently, three types of additives including suppressor represented by macromolecular polyether compounds (such as polyethylene glycol (PEG) [8][9][10], polypropylene glycol [11,12]), accelerator represented by propane sulfonate derivatives (such as sodium 3-mercapto-1propane sulfonate [13,14] and bis (3-sulfopropyl) disulfide (SPS) [15][16][17]), levelers represented by heterocyclic or alkyl compounds (such as Janus Green B, Diazine Black and Alcian Blue [18][19][20]). Among them, suppressors with larger molecular chains combine with Cl − and are usually adsorbed on the surface of the circuit board to form a chelate with Cu 2+ or Cu + to inhibit the deposition rate of copper, thereby reducing the current density of the blind hole orifice [8].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that there are many factors affecting the effect of blind hole filling, such as the formula of the electroplating solution (composition and concentration), electroplating process parameters (electroplating method, stirring mode, current density, and electroplating time), and the geometric size of blind hole (diameter and diameter depth ratio) [ 11 , 12 , 13 ]. However, there are not many reports about how to obtain a good blind hole filling effect for an HDI substrate by changing the content and proportion of copper sulfate and sulfuric acid in the plating solution formula, and the available references are very limited.…”
Section: Introductionmentioning
confidence: 99%